Praktik Perceraian di bawah Tangan Masyarakat Desa Palipan Kecamatan Sungai Manau Kabupaten Merangin Ditinjau dari Undang-undang Perkawinan No. 1 Tahun 1974 - Dewi Patimah; Hermanto Harun; D.I. Ansusa Putra (NALAR FIQH: Jurnal Hukum Islam, 2022)
This paper aims to determine the practice of divorce among the Palipan village community, Sungai Manau District, Merangin Regency, and also to find out how unregistered divorce according to Marriage Law No. 1 of 1974. This type of research is field research, namely research conducted directly to the field in order to obtain complete and valid data. Data collection techniques are interviews and documentation. The research methodology used is a qualitative research methodology and the approach that the authors use in this study uses a normative and comparative approach. Data collection in this study was carried out using observation, interview and documentation techniques. The results of this study indicate that the practice of divorce under the hands of the Palipan village community, Sungai Manau sub-district, Merangin Regency is the practice of divorce being carried out at home and attended by witnesses from both men and women. Factors that cause unregistered divorce of the Palipan village community are religious factors and customary factors, the divorce process is easy, fast and does not cost money, court location factors, lack of information, economic consequences, factors not compatible with family and personal problem factors. which must be covered. The implementation of the practice of unregistered divorce of the Palipan village community in the legal context of Law No. 1 of 1974 is considered illegal because it is not in accordance with the provisions of divorce stipulated in the Marriage Law No. 1 of 1974 article 39 paragraph 1.